They fought at Anzio - Eisenhower, John S. D., 1922- (University of Missouri Press, 2007)
"Eisenhower examines the Allies' Italian campaign--which included some of World War II's longest and bloodiest battles--with an emphasis on the Anzio offensive from the perspectives of the individuals who fought, both commanders and foot soldiers, highlighting his analysis with quotations from personal accounts and memoirs"--Provided by publisher.